Aqueous Leaching of Organic Acids and Dissolved Organic Carbon from Various Biochars Prepared at Different Temperatures. Issue 2 (1st March 2015) - Liu, Peng; Ptacek, Carol J.; Blowes, David W.; Berti, William R.; Landis, Richard C.
Abstract : Biochar has been used as a soil amendment, as a water treatment material, and for carbon (C) sequestration. Thirty‐six biochars, produced from wood, agricultural residue, and manure feedstocks at different temperatures, were evaluated for the aqueous leaching of different forms of soluble C. The release of inorganic C (alkalinity), organic acids (OAs), and total dissolved organic C (DOC) was highly variable and dependent on the feedstock and pyrolysis temperature. The pH and alkalinity increased for the majority of samples. Higher pH values were associated with high‐temperature (high‐T) (600 and 700°C) biochars. Statistically significant differences in alkalinity were not observed between low‐temperature (low‐T) (300°C) and high‐T biochars, whereas alkalinity released from wood‐based biochar was significantly lower than from others. Concentrations of OAs and DOC released from low‐T biochars were greater than from high‐T biochars. The C in the OAs represented 1 to 60% of the total DOC released, indicating the presence of other DOC forms. The C released as DOC represented up to 3% (majority <0.1%) of the total C in the biochar. Scanning electron microscopy with energy dispersive X‐ray spectroscopy showed the high‐T biochars had a greater proportion of micropores. Fourier transform infrared spectroscopy showed that hydroxyl, aliphatic, and quinone were the predominant functional groups of all biochars and that the abundance of other functional groups was dependent on the feedstock. The release of DOC, especially bioavailable forms such as OAs, may promote growth of organisms and heavy metal complexation and diminish the potential effectiveness of various biochars for C sequestration.